Individualized guidance and telephone monitoring in a self-supervised home-based physiotherapeutic program in Parkinson - Ihana Thaís Guerra de Oliveira Gondim; Carla Cabral dos Santos Accioly Lins; Nadja Maria Jorge Asano; Amdore Guescel C Asano; Etenildo Dantas Cabral; Maria das Graças Wanderley de Sales Coriolano
Abstract Introduction: Home therapeutic exercises have been a target of interest in the treatment of the Parkinson's disease (PD). The way that the physical therapist guides and monitors these exercises can impact the success of therapy. Objective: To evaluate the effects of individualized orientation and monitoring by telephone in a self-supervised home therapeutic exercise program on signs and symptoms of PD and quality of life (QoL). Methods: Single-blind randomized clinical trials with 28 people with PD (Hoehn and Yahr 1 to 3). Patients were randomized into two groups: experimental and control. The experimental group had a meeting with individualized guidance about physiotherapy exercises present in a manual, received the manual to guide their activities at home and obtained subsequent weekly monitoring by telephone. The control group received the usual cares by the service. Both were orientated to carry out exercises three times a week during 12 weeks. Was evaluated: (1) activities of daily living (ADL) and motor examination sections of the Unified Parkinson's Disease Rating Scale (UPDRS) and QoL by the Parkinson Disease Questionnaire 39 (PDQ-39). The analysis between groups was performed by the Mann-Whitney test and intragroup through the Wilcoxon (p < 0.05). Results: Significant improvement in ADL (p= 0.001) and motor examination (p= 0.0008) of the UPDRS, PDQ-39 total (p = 0.027) and dimensions mobility (p = 0.027), emotional well-being (p= 0.021) and bodily discomfort (p = 0.027) in the experimental group compared to the control group. Conclusion: The individualized guidance and weekly monitoring by telephone in a self-supervised home therapeutic exercises program promoted positive effects on ADL, motor examination and QoL of people in early stages of PD.